2017
DOI: 10.1080/24750573.2017.1403712
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between temperament and character dimensions of personality and burnout and management in healthcare organization workers

Abstract: Objective: Although most burnout research has focused on environmental job-related correlates, it is possible that personality factors also play an important role in the development of burnout. The aim of present study is to examine the relationship between personality and burnout in healthcare workers by using Cloninger's psychobiological model and Maslach's three-dimensional burnout model in a healthcare worker sample in Turkey. Methods: Our samples consisted of 66 male, 14 female and totally 80 healthcare o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…33,34 There has been debate on whether emotional exhaustion causes people to use EMO or situations or people that use EMO have a high chance of emotional exhaustion. 35 Devebakan et al 36 showed that low SD scores were significantly associated with burnout, and those with low scores often thought of themselves as worthless. Furthermore, Yazici et al 37 showed that high NS was positively correlated with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 There has been debate on whether emotional exhaustion causes people to use EMO or situations or people that use EMO have a high chance of emotional exhaustion. 35 Devebakan et al 36 showed that low SD scores were significantly associated with burnout, and those with low scores often thought of themselves as worthless. Furthermore, Yazici et al 37 showed that high NS was positively correlated with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with low self-esteem more frequently experience burnout (Devebakan et al, 2018). According to the conservation of resources (COR) theory, these individuals underestimate their internal resources, are less resistant to failure and negative emotions, and usually attribute particular events and achievements not to themselves but to persons occupying superior positions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Personality traits have a direct relationship with the degree of burnout in medical students and residents (3,4). A study among health care staff based on the Cloninger questionnaire and Mazlach's questionnaire, showed that personality traits can predict the incidence of burnout (5). Studies have revealed that some people with high IQs are not suitable for certain fields of study or work, because they lack certain personality traits, but they can instead achieve significant success in other academic and career environments.…”
mentioning
confidence: 99%